Pentingnya Scavenging Inspection Terhadap Kondisi Piston Ring Mesin Induk di MV. Melchior Schulte - Khaeroman, Khaeroman; Dwi Ratnandari, Septina; Bayu Wantoro, Widar; Masriah, Masriah; Susanti, Susanti; Faizal Reza, Bela (PPPM Polimarin, 2024)
This article discusses the importance of carrying out scavenging inspections on main engines on MV. Melchior Schulte, during the M/E scavenging inspection, a problem was discovered in cylinder number 3, namely a broken piston ring which was caused by a lack of cylinder oil lubrication in the cylinder liner. The aim of this research is to find out the correct procedures for carrying out main engine scavenging inspections and to find out the usefulness of carrying out main engine scavenging inspections. This research uses a descriptive method, by describing, describing systematically and accurately the nature, facts and relationships between the phenomena being studied, and tends to focus attention on solutions and solutions to actual problems as they existed at the time the research was carried out. The research results showed that the procedure and time for carrying out M/E scavenging inspection must follow or comply with the provisions in the M/E manual book, with the maximum running hours on the main engine being 500 hours, and the factors that influence the implementation of M/E scavenging were obtained. inspection, namely the main engine experienced a breakdown maintenance moment due to a clogged hole occurring in the injector in cylinder number 3 and a broken piston ring cermet number 4 in cylinder number 3 on the main engine